2022
DOI: 10.1371/journal.pbio.3001759
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a–Vangl1/2 signaling regulates the position and direction of lung branching through the cytoskeleton and focal adhesions

Abstract: Lung branching morphogenesis requires reciprocal interactions between the epithelium and mesenchyme. How the lung branches are generated at a defined location and projected toward a specific direction remains a major unresolved issue. In this study, we investigated the function of Wnt signaling in lung branching in mice. We discovered that Wnt5a in both the epithelium and the mesenchyme plays an essential role in controlling the position and direction of lung branching. The Wnt5a signal is mediated by Vangl1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
5
3
Order By: Relevance
“…It was also reported that mutational activation of RAS, a critical effector of ERK, controls mitotic spindle orientation in epithelium and consequently affects the thickness to length ratio of the early lung epithelium, independently of proliferative activity and cell shape changes (66). As this report suggested the involvement of planar cell polarity (PCP) in controlling duct shape, subsequent experimental studies have indicated that PCP components affect lung epithelial morphology (6770). The components of the PCP pathway are involved in Wnt signaling-mediated cytoskeletal regulation, directing cell shape changes and migration (71).…”
Section: Discussionmentioning
confidence: 97%
“…It was also reported that mutational activation of RAS, a critical effector of ERK, controls mitotic spindle orientation in epithelium and consequently affects the thickness to length ratio of the early lung epithelium, independently of proliferative activity and cell shape changes (66). As this report suggested the involvement of planar cell polarity (PCP) in controlling duct shape, subsequent experimental studies have indicated that PCP components affect lung epithelial morphology (6770). The components of the PCP pathway are involved in Wnt signaling-mediated cytoskeletal regulation, directing cell shape changes and migration (71).…”
Section: Discussionmentioning
confidence: 97%
“…Whole-mount immunostaining was performed as previously described 48 , 49 . Briefly, the embryonic lungs at the indicated time points were collected and fixed in 4% PFA on ice for 1 h. Samples were washed with 0.1% Tween-20/PBS for 30 min then dehydrated in graded methanol solutions (25%, 50%, 75%, 100%).…”
Section: Methodsmentioning
confidence: 99%
“…Our molecular understanding of lung development has advanced through the identification of multiple players in this process and elucidation of their mechanisms of action. Major signaling pathways, including the Hedgehog (Hh), [13] Wnt (canonical and non-canonical), [14,15] Fibroblast growth factor (FGF), [16][17][18] Transforming growth factor (TGF), Bone morphogenetic protein (BMP), [19] Platelet-derived growth factor (PDGF), Hippo, [20,21] Vascular endothelial growth factor (VEGF), [22] and mTOR (mechanistic target of rapamycin) [23] signaling pathways, have been shown to control one or more aspects of lung cell proliferation, migration and differentiation, and cell-cell and cellmatrix interactions (Figure 1B). In this regard, various models, such as differential cell growth, cortical constriction, and smooth muscle differentiation, have been proposed as processes that initiate new lung branches.…”
Section: An Overview Of Lung Branching Morphogenesis and Cell Type Sp...mentioning
confidence: 99%